Predictive factors of early mortality after transcatheter aortic valve implantation: individual risk assessment using a simple score. Issue 13 (16th April 2014) - Iung, Bernard; Laouénan, Cédric; Himbert, Dominique; Eltchaninoff, Hélène; Chevreul, Karine; Donzeau-Gouge, Patrick; Fajadet, Jean; Leprince, Pascal; Leguerrier, Alain; Lièvre, Michel; Prat, Alain; Teiger, Emmanuel; et al.
Abstract : Objective: Decision making for intervention in symptomatic aortic stenosis should balance the risks of surgery and of transcatheter aortic valve implantation (TAVI). We identified the factors associated with early mortality after TAVI and aimed to develop and validate a simple risk score. Methods: A population of 3833 consecutive patients was randomly split into two cohorts comprising 2552 and 1281 patients, used respectively to develop and validate a scoring system predicting 30-day or in-hospital mortality. Results: TAVI was performed using the Edwards Sapien prosthesis in 2551 (66.8%) patients and the Medtronic Corevalve in 1270 (33.2%). Approach was transfemoral in 2801 (73.4%) patients, transapical in 678 (17.8%), subclavian in 219 (5.7%) and other in 117 (3.1%). Early mortality was 10.0% (382 patients). A multivariate logistic model identified the following predictive factors of early mortality: age ≥90 years, body mass index <30 Kg/m 2, New York Heart Association class IV, pulmonary hypertension, critical haemodynamic state, ≥2 pulmonary oedemas during the last year, respiratory insufficiency, dialysis and transapical or other (transaortic and transcarotid) approaches. A 21-point predictive score was derived. C-index was 0.67 for the score in the development cohort and 0.59 in the validation cohort. There was a good concordance between predicted and observed 30-day mortality rates in the development and validation cohorts. Conclusions: Early mortality after TAVI is mainly related to age, the severity of symptoms, comorbidities and transapical approach. A simple score can be used to predict early mortality after TAVI. The moderate discrimination is however a limitation for the accurate identification of high-risk patients.